Glycyrrhizic acid modified Poria cocos polyscaccharide carbon dots dissolving microneedles for methotrexate delivery to treat rheumatoid arthritis - Chen, Qi; Wu, Chengyuan; Wang, Siwei; Wang, Qiang; Wu, Peiyun; Wang, Lei; Yan, Peiyu; Xie, Ying (Frontiers in Chemistry, 2023)
Rheumatoid arthritis was a inveterate phlogistic joint disease. Among the antirheumatic drugs, methotrexate was one of the most effective drugs often recommended, but the adverse reaction caused by oral and injection medication of methotrexate greatly limit its clinical practice. Administration through the skin provides an ideal alternative method for traditional drug delivery. In this study, Poria cocos polysaccharide derived carbon dots was synthesized by one-step hydrothermal method, the anti-inflammatory drug glycyrrhizic acid was modified onto the carbon dots by amide reaction, and then the anti-rheumatic drug methotrexate was loaded by intermolecular force to prepare a nano-drug loading system with fluorescence and double anti-inflammatory effects; Finally, dissolving microneedles were fabricated by using hyaluronic acid as matrix materials to realize transdermal drug delivery. After the microneedles was implanted into the skin tissue, the microneedle tip was degraded, so that the loaded nanoparticles can be released, carbon dots achieved fluorescence localization, glycyrrhizic acid and methotrexate exerted anti-inflammatory effects. The surface morphology and structure of the glycyrrhizic acid modified carbon dots loaded methotrexate nanosystem were characterized by transmission electron microscopy, fluorescence spectroscopy, Laser Nanometer Particle Size Analyzer, UV-vis absorption spectroscopy, fourier transform infrared spectroscopy, differential scanning calorimeter and nuclear magnetic resonance spectrometer. The results showed that glycyrrhizic acid and methotrexate were successfully loaded onto carbon dots. The results showed that the nanoparticles had high drug loading (~49.09%) and good release rate. The cumulative release was ~65.5% at pH 5.0, the amount of ~92% at pH 7.4. RAW264.7 cells were induced with lipopolysaccharide to found an inflammatory cell model. The results of extracorporeal cell experiments showed that the toxicity of glycyrrhizic acid-modified carbon dots was low. After loading methotrexate, the nano-drug delivery system showed a stronger inhibitory effect on lipopolysaccharide-induced inflammatory model cells than free methotrexate, and the secretion of proinflammatory cytokines such as IL-1β, TNF-α and IL-6 were visibly abatemented. After the nanosystem was prepared into microneedles, it could penetrate the skin to achieve transdermal drug delivery. The drug release effect was good and the curative effect was significant. The ideal therapeutic results were obtained in the rheumatoid rat model.